Learning about the term structure and optimal rules for inflation targeting - Mewael F. Tesfaselassie; Eric Schaling; Sylvester C. W. Eijffinger (Center for Economic Research, 2006)
In this paper we incorporate the term structure of interest rates in a standard inflation forecast targeting framework.We find that under flexible inflation targeting and uncertainty in the degree of persistence in the economy, allowing for active learning possibilities has effects on the optimal interest rate rule followed by the central bank.For a wide range of possible initial beliefs about the unknown parameter, the dynamically optimal rule is in general more activist, in the sense of responding aggressively to the state of the economy, than the myopic rule for small to moderate deviations of the state variable from its target. On the other hand, for large deviations, the optimal policy is less activist than the myopic and the certainty equivalence policies.
urn:nbn:nl:ui:12-193482
Keywords: 330; Learning; Rational Expectations; Separation Principle; Term Structure of Interest Rates; Inflation Targeting; Zinsstruktur; Rationale Erwartung; Lernen; Geldpolitik; Theorie